2022
DOI: 10.1186/s40900-022-00394-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-creation of new knowledge: Good fortune or good management?

Abstract: Background Potential solutions to bridging the research practice gap include collaborative frameworks and models. Yet there is little evidence demonstrating their application in practice. In addressing this knowledge gap, this in-depth case study explored how the co-creation of new knowledge framework and its four collaborative processes (co-ideation, co-design, co-implementation, and co-evaluation) are utilised to support people who had attempted suicide through an Australian psychoeducational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Drawn from these findings, the authors identified six main points which form the basis of this discussion. These include (1) the fact that the necessary time and resources required to commit to co-design process completion adequately were underestimated at the outset, (2) there is a need to support the health, well-being and dignity of lived experience expert participants, (3) academic ethical processes have yet to adapt to address more participatory and integrated research methods, (4) strategies used to foster strong collaborative relationships across a diverse group were valued by all participants, (5) better delineation between terminologies such as codesign and community-based participatory research or patient and public involvement would improve the clarity of research methods and author intent and, (6) broader non-traditional impacts that participatory research can create should be better quantified and valued in the context of research impact. Each point will now be discussed in further detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Drawn from these findings, the authors identified six main points which form the basis of this discussion. These include (1) the fact that the necessary time and resources required to commit to co-design process completion adequately were underestimated at the outset, (2) there is a need to support the health, well-being and dignity of lived experience expert participants, (3) academic ethical processes have yet to adapt to address more participatory and integrated research methods, (4) strategies used to foster strong collaborative relationships across a diverse group were valued by all participants, (5) better delineation between terminologies such as codesign and community-based participatory research or patient and public involvement would improve the clarity of research methods and author intent and, (6) broader non-traditional impacts that participatory research can create should be better quantified and valued in the context of research impact. Each point will now be discussed in further detail.…”
Section: Discussionmentioning
confidence: 99%
“…Co-production was chosen as the planning method for the study, as the inclusion of community members (Rocky Bay Lived experience experts and Staff ) in each step of Fig. 1 Summary of telepractice co-design project structure [1] the research process would increase buy-in and make the research more likely to meet their needs [5]. An example of co-planning (part of co-production) includes the study steering committee, with a lived experience expert, clinician and project sponsor representatives collaborating on the selection of study aim, methods and recruitment processes.…”
Section: Process Of Co-production and Preparation For Co-designmentioning
confidence: 99%
See 2 more Smart Citations
“…The support offered to the SDG and FIG sites was framed to bridge potential gaps between current practice and optimal conditions for person-centred patient participation [ 29 ]. In addition, the FIG strategy was incorporated in the study to test whether local support (by means of IFs being trained) would trump dissemination of a support package for managers.…”
Section: Methodsmentioning
confidence: 99%